Analisis Tantangan dan Hambatan dalam Penegakan Hukum Angkutan Antar Provinsi - Avid Wahyudi Ibrahim; Ibrahim Ahmad; Roy Marthen Moonti (Lembaga Pengembangan Kinerja Dosen, 2024)
Law enforcement of inter-provincial transportation in Indonesia faces significant challenges and obstacles. This study aims to identify factors that hinder effective law enforcement in the inter-provincial transport sector. The main findings indicate weaknesses in the supervision of transport companies, lack of coordination between relevant agencies, and limited trained human resources. In addition, illegal practices such as unlicensed transportation, the use of non-standard vehicles, and low public awareness of regulations, exacerbate the situation. Therefore, more assertive and consistent law enforcement is needed, as well as increased coordination between relevant parties to create a safer, more efficient inter-provincial transportation system that complies with existing regulations.